The complexity of the antecedents influencing accountability in organisations. Issue 4 (12th June 2017) - Pearson, Hayley; Sutherland, Margaret
Abstract : Purpose: Business, society and academic literature all show an increase in the demand for greater accountability. Although accountability is deemed to be central to performance in the workplace, it is an ever-expanding, complex and elusive phenomenon. There is very little empirical research in human resource literature on accountability's wide-ranging antecedents and how they are best implemented. This paper aims to set out to identify which factors have the greatest influence when holding an individual to account. Design/methodology/approach: Qualitative, exploratory research methods were adopted. Twenty semi-structured, in-depth interviews were conducted with CEO's, executives, human resource experts, senior managers and consultants in eight industries in South Africa. The data were analysed by thematic content analysis. Findings: The findings identified five dominant antecedents that are required to effectively hold an individual to account for their performance. These are the culture and leadership of the organisation, the systems in the organisation, the values and recruitment means of the individual and the clarity of role. For each of these factors, the key management mechanisms were identified. Research limitations/implications: The study was done in one country (South Africa) and only with senior executives. Practical/implications: A "System of Accountability" model was developed depicting the interdependence of the factors and conceptualising a process that can be followed for human resource professionals and senior management to develop a culture of accountability. Originality/value: There is a dearth of literature and empirical research on how to implement a combination of systems to ensure accountability in the workplace. This research offers some solutions to that gap in the literature.